A percepção dos Stakeholders sobre as ações de responsabilidade social empresarial: análise de uma empresa de fruticultura em Mossoró/RN - Brito Filho, Arrilton Carlos de (Universidade Federal Rural do Semi-Árido, 2016)
This study aims to compare the differences in perception among stakeholders in relation to Corporate Social Responsibility actions in a fruit growing company in Mossoró/RN. The work brings a discussion of the concepts often differ on the social responsibility, the theoretical models proposed by Schwartz and Carroll (2003) and Melo Neto and Froes (2001), as well as the importance to the contradictions of fruticultora activity. It is a study of qualitative approach, as to the purposes, refers to a descriptive research, with regard to the means it is a field of research, which will be developed in two phases: in the first stage was carried out the survey the productive and social profile of the companies affiliated to the COEX, located in agropolo grower Mossoró/Assu to identify companies to be investigated; the second time was conducted semi-structured interviews with managers and stakeholders of Agro melon Mossoro (pseudonym). The results indicate that CSR practices developed by Agro melon Mossoro, reflecting the perceptions of its stakeholders, provides consistency with the principles of theoretical models Schwartz and Carroll (2003) and Melo Neto and Froes. Their actions are guided by economic, legal and ethical reasons, however, there is a rooting CSR in the economic dimension causing the other dimensions are achieved or met in a secondary perspective, almost a cause consequence, improving the economic dimension
Perceptions of Stakeholders on the liability of actions corporate social analysis of a company in fruit Mossoró / RN
Keywords: Responsabilidade Social; Fruticultura; Stakeholders; Social Responsibility; Fruit production; Stakeholders; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE